Augmented reality tools and learning practice in mobile-learning - Figueiredo, Mauro (2017)
There are many augmented reality (AR) applications available that can be used to create educational contents for these mobile devices. This paper surveys the most popular augmented reality applications and we select AR eco-systems to be used in daily teaching activities which are user friendly, do not require programming skills and are free. Different augmented reality technologies are explored in this paper to create teaching activities with animations, videos and other information to be shown on top of interactive documents. It is presented the creation of a novel augmented reality book that was developed with teachers and students. Several examples are also presented that are used in educational activities, from kindergarten to elementary and secondary schools, to improve reading, comprehension and learning of music.